PENGARUH PELAYANAN BSI MOBILE TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION (Studi pada Pengguna BSI Mobile KCP Bandung Setrasari) - Kamelia, Syifaul; Amran, Kiagus Muhammad; Aziz Sugiharto, Nur (JURNAL ILMIAH EDUNOMIKA, 2024)
In striving for customer loyalty, banks are obliged to provide excellent service for their customers. From this satisfactory service, the level of customer satisfaction will increase and create loyalty for a product or service. This study aims to find out The Effect of BSI Mobile Services on Customer Loyalty Through Customer Satisfaction in Bank Syariah Indonesia KCP Bandung Setrasari customers who use BSI Mobile. The research method used is quantitative research using the type of associative research. The population in this study is all customers of Bank Syariah Indonesia KCP Bandung Setrasari who use BSI Mobile. The sampling technique used in this study is Purposive Sampling with a sample of 120 respondents. The data collection technique uses a questionnaire that will be tested for validity and reliability. The data analysis used in this study is path analysis using SPSS 26 software. The results of the study show that BSI Mobile services have a positive and significant effect on customer satisfaction, BSI Mobile services have a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, and customer satisfaction is able to mediate the influence of BSI Mobile services on customer loyalty.